Exploring drivers to engage in fashion luxury consumption - Loureiro, S (2022)
The main purpose of the current study is to analyze how desire, perceived-self, social values and involvement are related to consumer engagement into the fashion luxury industry. A sample of 295 luxury fashion consumers participate in the study. Findings suggest that perceived-self is not one of the most significant driver to consumer engagement. Subjective well-being may also act as an outcome of consumer engagement. The article also provides managerial implications, limitations and further research.